SAT0025 Evolution of psoriatic arthritis with distal interphalangeal joints involvement at onset. (1st June 2001) - Montilla, CA; González, CM; López-Longo, FJ; Castillo, R; Caro, N; González-Montagut, C; Cebrián, L; Gómez, S; Carmona, E; Monteagudo, I; Carreño, L
Abstract : Background: Distal interphalangeal joints (DIP) arthritis described by Moll and Wright as a psoriatic arthritis (Psa) pattern is now considered an evolutionary step towards other classification patterns. Objectives: To study the clinical and radiological evolution of a group of patients with arthritis limited to the DIP as onset of Psa. Methods: We have studied the clinical and radiological evolution of 204 patients diagnosed with Psa (Moll and Wright criteria) during the first year of the disease selecting those patients whose initial clinical features were exclusively arthritis of the DIP. The radiological findings after one-year follow-up were classified into stages according to Steinbrocker´s criteria. Results: Arthritis of DIP as onset of the disease was found in 19/204 (9.3%) of the patients. The mean age at onset was 49 years (range: 34–64). Psoriasis before arthritis onset was present in 8/19 (42.1%) and in 9/19 (47.3%) the onset of arthritis and psoriasis was simultaneous. Onychodystrophy (pitting) was present in 7/19 (36.8%). After one-years 9/19 (47.3%) patients continued with arthritis as the only manifestations of Psa, 8/19 (42.1%) patients evolved toward other arthritis patterns (5 asymmetrical oligoarthritis and 3 symmetrical polyarthritis). The joints more commonly involved along with the DIP were metacarpophalangeal (75%) and proximal interphalangeal (62.5%). 2/19 patients (10.4%) did not show DIP arthritis after one year. At the end of the one-year study 9/19 (47, 3%) of the patients were classified into III stage radiological criteria, 2/19 (10.4%) were at the stage I and in the remaining patients radiological was considered as normal. Conclusion: Almost half of the patients with DIP arthritis as Psa onset evolve within one year towards others arthritis patterns. Half of the patients revealed an aggressive radiological progression during the first year of the disease.